2014
DOI: 10.1007/978-3-319-10705-9_19
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Parareal for the Navier-Stokes Equations Depending on the Reynolds Number

Abstract: Abstract. The paper presents first a linear stability analysis for the time-parallel Parareal method, using an IMEX Euler as coarse and a Runge-Kutta-3 method as fine propagator, confirming that dominant imaginary eigenvalues negatively affect Parareal's convergence. This suggests that when Parareal is applied to the nonlinear Navier-Stokes equations, problems for small viscosities could arise. Numerical results for a driven cavity benchmark are presented, confirming that Parareal's convergence can indeed dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…For these problems there is a high demand for highly efficient parallel solvers [53]. The Parareal algorithm was for example reported to perform poorly in advection-dominated problems [18,49]. Figure 4.6 illustrates that widening the spectrum does not significantly affect the convergence of the PEBK iterations.…”
Section: Parallel Efficiencymentioning
confidence: 99%
“…For these problems there is a high demand for highly efficient parallel solvers [53]. The Parareal algorithm was for example reported to perform poorly in advection-dominated problems [18,49]. Figure 4.6 illustrates that widening the spectrum does not significantly affect the convergence of the PEBK iterations.…”
Section: Parallel Efficiencymentioning
confidence: 99%
“…Figure 4.16b indicates that a parallel speedup can be also achieved for ν = 10 −3 and ν = 10 −4 . The parallel efficiency of the Parareal algorithm is known to deteriorate for similarly small viscosity coefficients [161]. Furthermore, we note that the actual parallel efficiency of the PEBK method may even be better in practice, since the required number of PEBK iterations could decrease with higher P .…”
Section: Parallel Efficiencymentioning
confidence: 99%
“…Although, the performance in some cases can be improved by Krylov subspace enhancement [47,57,144]. In fluid flow problems, it was demonstrated that the performance of Parareal deteriorates in cases with low viscosity [49,100,161]. Direct numerical simulation at high Reynolds number then becomes challenging because convection in the turbulent flow becomes an important term and the high Reynolds number leads to small dissipation.…”
Section: Parallelism In Timementioning
confidence: 99%
See 2 more Smart Citations